What is the Role of Carbon Taxes in Climate Change Mitigation? (revised) - Aldy, Joseph; Ley, Eduardo; Parry, Ian (World Bank, Washington, DC, 2014)
This note argues that a carbon tax system is more practical to implement, monitor, and enforce than tradable permit-based approaches to global climate-change action. It suggests that a sensible design will be an upstream carbon tax on the fossil fuel supply chain, which can also include other major non-carbon dioxide (CO2) greenhouse gases (GHGs). While risks such as fiscal cushioning exist, a tax-based system will be more transparent and offer the appropriate incentives for participation and compliance.